2020
DOI: 10.1007/s13555-020-00413-8
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Treatment Patterns Among Patients with Atopic Dermatitis Using Advanced Therapies in the United States: Analysis of a Retrospective Claims Database

Abstract: Introduction: For many, atopic dermatitis (AD) is not adequately controlled with topical regimens. This analysis examined treatment using advanced therapies and associated costs. Methods: The IQVIA Health Plan Claims data set was analyzed. Patients aged C 12 years with AD who newly initiated advanced therapy after the availability of dupilumab (March 28, 2017) and had C 6 months continuous enrollment before and after their first advanced therapy claim (index date) were included. Advanced therapies included dup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 23 publications
5
29
1
Order By: Relevance
“… 1 , 2 Affecting up to 20% of children and 10% of adults globally, 3 , 4 AD is significantly associated with decreased levels of health‐related quality of life (QoL), 5 , 6 increased work‐related impairment 5 , 7 and high healthcare costs. 8 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Affecting up to 20% of children and 10% of adults globally, 3 , 4 AD is significantly associated with decreased levels of health‐related quality of life (QoL), 5 , 6 increased work‐related impairment 5 , 7 and high healthcare costs. 8 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the Japanese and international AD guidelines discourage the long‐term use of systemic corticosteroids because of severe side effects, 16 especially in children, 17 but the results of the current study showed that oral corticosteroid use is approximately 8% in Japan. A recent analysis of a US claims database showed similar results, with 73.4% of patients who initiated treatments associated with moderate‐to‐severe AD beginning treatment with a systemic corticosteroid 18 . For short‐term management (≤1 week) of AD, clinicians might use oral corticosteroids in patients with severe AD because of the low cost and lack of better treatment options, 16 highlighting the need for alternative treatments.…”
Section: Discussionmentioning
confidence: 87%
“…As severity of the disease is not coded in administrative registers, this study defined severity based on concurrent treatment employed in a previously published study [ 31 ]. Patients with systemic treatments (corticosteroids and non-corticosteroid immunosuppressants) were considered to have a severe form of AD and are presented separately in this publication for reference [ 31 ].…”
Section: Methodsmentioning
confidence: 99%